STUDENTS PERSPECTIVE ON ASYNCHRONOUS AND SYNCHRONOUS TYPE OF E- LEARNING AT BAN OOM SCHOOL THAILAND - Ervi Ananda Ayu Rahmadani; Ribeh Najib Muhammad (Universitas Kuningan, 2021)
During Covid-19 pandemic, the main focus of education is distance learning. Especially for learning strategy. In this research, the researcher used two strategies; synchronous focuses on e-learning using Zoom and asynchronous using video material. Researchers used two of strategies to measure which strategy is more effective to assist students in facilitating e-learning process. The process also aimed to reach students and teach them from home during quarantine. This paper examined students' perceptions of e-learning using synchronous (zoom) and asynchronous (video material) at Ban Oom school of Thailand. The students have experience of implementing the strategies 4 (four) months during e-learning. There are 25 students participated on the learning process. The study used quantitative and qualitative design with triangulation approaches, with the analysis instrument being a questionnaire with Likert scale questions. According to the findings of the observations, there are three activity factors (communication, learning materials and the learning process). The analysis instrument is a questionnaire consisting of Likert scale questions. The findings from the questionnaire showed positive answers to all the three factors. The students agreed that they can communicate easily. It shows that students have a high perspective on synchronous learning with various advantages compared to asynchronous learning where learning by watching videos that sent by the teacher and cannot interact directly if there are something is not understood by the students.Keywords: students’ perspective; asynchronous and keyword synchronous; e-learning.